Region-Adaptive Deformable Registration of CT/MRI Pelvic Images via Learning-Based Image Synthesis - Cao, Xiaohuan; Yang, Jianhua; Gao, Yaozong; Wang, Qian; Shen, Dinggang (IEEE transactions on image processing, 2018)
Registration of pelvic computed tomography (CT) and magnetic resonance imaging (MRI) is highly desired as it can facilitate effective fusion of two modalities for prostate cancer radiation therapy, i.e., using CT for dose planning and MRI for accurate organ delineation. However, due to the large intermodality appearance gaps and the high shape/appearance variations of pelvic organs, the pelvic CT/MRI registration is highly challenging. In this paper, we propose a region-adaptive deformable registration method for multimodal pelvic image registration. Specifically, to handle the large appearance gaps, we first perform both CT-to-MRI and MRI-to-CT image synthesis by multi-target regression forest. Then, to use the complementary anatomical information in the two modalities for steering the registration, we select key points automatically from both modalities and use them together for guiding correspondence detection in the region-adaptive fashion. That is, we mainly use CT to establish correspondences for bone regions, and use MRI to establish correspondences for soft tissue regions. The number of key points is increased gradually during the registration, to hierarchically guide the symmetric estimation of the deformation fields. Experiments for both intra-subject and inter-subject deformable registration show improved performances compared with the state-of-the-art multimodal registration methods, which demonstrate the potentials of our method to be applied for the routine prostate cancer radiation therapy.